Legislature and Governance A Comparative Study between Bangladesh and Japan - Bikram Biswas; Md. Shamsul Arefin; Sajib Kumar Roy; Mohammad Nur Ullah (Journal of Governance, 2021)
This study shades light on the legislative structure and practices of Japan and that of Bangladesh with a view to comparing the state of governance of these two countries. This study has been conducted based on purely qualitative approach with content analysis. As per myriad of study legislative practices of Japan is successful to discharge good governance as the economic growth of Japan is termed as miracle. This study find that the legislative practices of Japan incorporated all the values of governance through its provision of two-house diet where lower house preserve substantial power over upper house, floor crossing, responsiveness of the legislatures, and strong role of parliamentary committees. After comparing the legislative practices of Japan with that of Bangladesh, this study basically found distinctions in structure and practiced value. The parliamentarian of Japan can vote against party decision to preserve the national interest while this is restricted in Bangladesh by the constitution. Japanese parliamentarian even prime minister often stepped down from the government confessing their faults. In Bangladesh we can’t even think of it. Although every parliament in Bangladesh forms myriad of committees to oversight the work of ministers but visible and vibrant role of these committees is rare in both in giving policy input and in discharging oversight activities. Bangladesh, a democratic state wants to uphold the principles of good governance, may imitate some legislative principles both from structure and values of Japanese style of legislature.Keywords: legislature; governance; good governance; Japan; Bangladesh